Immunomodulatory effects of oral administration of Aloe vera supplemented probiotic ice cream in mice - Yadav, Vidhu; Singh, RRB; Shaik, Abdul Hussain; Kapila, Suman (Indian Journal of Dairy Science, 2017)
Nutraceuticals possess immunomodulatory properties and generally act by stimulating both specific and non-specific immunity. Some of these stimulate both humoral and cell-mediated immunity, while others activate only the cellular components of the immune system. In the present investigation, immunomodulatory effects of Aloe vera supplemented probiotic ice cream (ASPIC) were evaluated in mice immunocompromised using cyclophosphamide. After 13 days of feeding period, percentage phagocytosis, lymphocyte proliferation index, IgA levels and lymphocyte count increased significantly (p